Jesse Bear, What Will You Wear? - Carlstrom, Nancy White; Degen, Bruce (New York : Macmillan, 1986)
Rhymed text and illustrations describe Jesse Bear's activities from morning to bedtime.
Keywords: Bears -- Fiction; Stories in rhyme